Electronic and structural properties of fluorene–thiophene copolymers as function of the composition ratio between the moieties: a theoretical study. Issue 31 (25th July 2018) - Benatto, L.; Marchiori, C. F. N.; da Luz, M. G. E.; Koehler, M.
Abstract : Through theoretical analysis, we study relevant properties of some molecular structures formed by oligothiophenes (T) and dioctylfluorenes (F) units, like the exciton binding energy ( E b ) and dipole moment, important for the efficiency of different kinds of optical and electronic devices. Abstract : Through theoretical analysis, we study relevant properties of some molecular structures formed by oligothiophenes (T) and dioctylfluorenes (F) units, commonly employed in the fabrication of different kinds of optical and electronic devices. For so, we first consider F–(T) n –F molecules with different numbers of thiophene rings ( n ). Among other characteristics, we calculate the dipole moment change between the ground and excited state (Δ μ ge ), a quantity that greatly influences the exciton dissociation and charge carrier mobility. We show that the planarity of the ground state geometry correlates Δ μ ge to the exciton binding energy ( E b ), with higher Δ μ ge 's corresponding to lower E b 's when n > 3. We also unveil a relevant dependence of Δ μ ge with the odd–even parity of n and that Δ μ ge assumes higher values when the molecule is composed by bithiophene (instead of simple thiophenes) moieties in the syn -conformation (with the two heteroatoms pointing in the same direction). From molecules results, we then address larger systems, formed by different oligomers of F–T copolymers containing blocks of dioctylfluorenes and bithiophenes (T2). We systematic investigate their electronic and structural properties as function of the composition ratio between the T2 and F moieties. Similar to the molecules, we deduce that the magnitude of Δ μ ge is higher for the syn conformer of the T2 unit. Moreover, the highest values of Δ μ ge are achieved when the number of the T2 increases relative to a fixed number of the F units in the mer. Such behaviors are in agreement and actually can qualitative explain measurements in the literature on the quantum efficiency of charge carrier generation in F–T copolymers. The present findings can be helpful in designing novel materials with improved photoelectric responses.